Pengaruh motivasi kerja dan iklim pada kinerja kerja karyawan dan kepuasan di Danau Toba Hotel International Medan - Lamminar Lamminar; Binur Pretty Napitupulu; Novia Ruth Silaen; Veramika Sembiring; Pandapotan Nauli Sun Siregar (Akademi Pariwisata Darma Agung, 2018)
This study aims to find out and analyze: The direct effect of motivation on job satisfaction at the Danau Toba International Hotel Medan ; Direct effect of work motivation on employee performance; The direct effect of the work climate on job satisfaction; the direct effect of the work climate on performance; Direct effect of job satisfaction on employee performance; Indirect effect of motivation on employee performance through job satisfaction; Indirect effect of work climate on performance through job satisfaction. Questionnaires were distributed to 124 respondents. Sample data were analyzed through structural equation modeling (SEM) with the maximum likelihood method. The research findings are: Motivation has a significant direct effect on job satisfaction at Danau Toba International Hotel (HDTI) Medan, with a coefficient of 0.967; Motivation has a significant direct effect on employee performance, with a coefficient of 1,778; Work climate has a direct effect not significant on job satisfaction, with a coefficient of -0.035; Work climate has a direct effect not significant on job satisfaction, with a coefficient of -0.097; Job satisfaction has a significant direct effect on employee performance, with a coefficient of -0.799; Work motivation does not have a significant indirect effect on performance through job satisfaction; The work climate has an indirect effect which is not synergistic on performance through job satisfaction.